Multiple sclerosis in Central America and Caribbean countries: frequency and clinical characterization of an emergent disease - Gracia, Fernando; Ramírez Navarro, Deyanira A.; Ramírez Sánchez, Nicia E.; Weiser, Roberto; Parajeles-Vindas, Alexander; Portillo Rivera, Ligia I.; Torres, Ericka López; García Valle, Luis A.; Sanabria-Castro, Alfredo; Abdón López, César; Araujo, Pahola; Ayerdis Zamora, Maria J.; et al. (Frontiers in Epidemiology, 2024)
Background: Multiple Sclerosis (MS) is a common neurological disease among white populations of European origin. Frequencies among Latin Americans continue to be studied, however, epidemiologic, and clinical characterization studies lack from Central American and Caribbean countries. Ethnicity in these countries is uniformly similar with a prevalent Mestizo population. Methods and Results: Data from January 2014 to December 2019 from Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica, Panama, Dominican Republic, and Aruba on demographic, clinical, MRI and phenotypic traits were determined in coordinated studies: ENHANCE, a population-based, retrospective, observational study on incidence and clinical characteristics, and from the subgroup with MS national registries (Aruba, Dominican Republic, Honduras, and Panama), data on prevalence, phenotypes and demographics. Expanded Disability Status Scale (EDSS), and therapeutic schemes were included. ENHANCE data from 758 patients disclosed 79.8% of Mestizo ethnicity; 72.4% female; median age at onset 31.0 years and 33.2 at diagnosis. The highest incidence rate was from Aruba, 2.3-3.5x100,000 inhabitants, and the lowest, 0.07-0.15x100,000, from Honduras. Crude prevalence rates per 100,000 inhabitants fluctuated from 27.3 (Aruba) to 1.0 (Honduras). Relapsing MS accounted for 87.4% of cases; EDSS < 3.0 determined in 66.6% (mean disease duration: 9.1 years, SD  5.0); CSF oligoclonal bands 85.7%, and 87% of subjects hydroxyvitamin D deficient. Common initial therapies were interferon and fingolimod. Switching from interferon to fingolimod was the most common escalation step. The COVID-19 pandemic affected follow-up aspects of these studies. Conclusion: This is the first study providing data on frequencies and clinical characteristics from 8 countries from the Central American and Caribbean region, addressing MS as an emergent epidemiologic disorder. More studies from these areas are encouraged.